Beyond the neural correlates of consciousness: using brain stimulation to elucidate causal mechanisms underlying conscious states and contents. Issue 1 (2nd January 2021) - Bareham, Corinne A.; Oxner, Matt; Gastrell, Tim; Carmel, David
ABSTRACT: We are conscious beings: Somehow, the activity of our brains and nervous systems gives rise to states in which we have subjective experiences; and when we are in such states, we are aware of specific content. Researchers are only beginning to develop an understanding of the neural mechanisms underlying these phenomena. Much of the research in the last few decades has focussed on discerning the neural correlates of consciousness, using neuroimaging methods. Correlates, however, are not causes: to draw inferences about the processes that generate consciousness, rather than accompanying it, one must manipulate brain activity and examine the effects this has on conscious states and contents. One way to do so is to use brain stimulation techniques, such as transcranial magnetic stimulation (TMS). In this review, we survey the consciousness literature with a special emphasis on TMS studies. We begin by examining what is known about the neural substrates of states of consciousness – the kinds of brain activity that determine whether a person is awake, asleep, or suffering from a disorder of consciousness. We then delve into the contents of consciousness, by examining the literature on perceptual awareness. Throughout, we highlight current controversies and promising avenues for further research.